Carbon monoxide prevents ventilator induced lung injury via caveolin-1 - Hoetzel, Alexander (2009)
OBJECTIVES: Carbon monoxide (CO) can confer anti-inflammatory protection in rodent models of ventilator-induced lung injury (VILI). Caveolin-1 exerts a critical role in cellular responses to mechanical stress, and has been shown to mediate cytoprotective effects of CO in vitro. We sought to determine the role of caveolin-1 in lung susceptibility to VILI in mice. Furthermore, we assessed the role of caveolin-1 in the tissue protective effects of CO in the VILI model. DESIGN: Prospective experimental study SETTING: University laboratory SUBJECTS: Wild type (wt) and caveolin-1 deficient (cav-(−/−)) mice INTERVENTIONS: Mice were subjected to tracheostomy and arterial cannulation. Wt and cav-1(−/−) mice were ventilated with a tidal volume of 12 ml/kg body weight and a frequency of 80/min for 5 min as control, or for 8h with air in the absence or presence of CO (250 parts per million). Bronchoalveolar lavage (BAL) and histology were used to determine lung injury. Lung sections or homogenates were analyzed for caveolin-1 expression by immunohistochemical staining or Western Blotting, respectively. MEASUREMENTS AND MAIN RESULTS: Ventilation led to an increase in BAL protein concentration, cell count, neutrophil recruitment, and edema formation that was prevented in the presence of CO. While ventilation alone slightly induced caveolin-1 expression in epithelial cells, the application of CO during the ventilation significantly increased the expression of caveolin-1. In comparison to wt mice, mechanical ventilation of cav-1(−/−) mice led to a significantly higher degree of lung injury as compared to wt mice. In contrast to its effectiveness in wt mice, CO-administration failed to reduce lung injury markers in cav-1(−/−) mice. CONCLUSIONS: Caveolin-1 null mice are more susceptible to VILI. Carbon monoxide executes lung protective effects during mechanical ventilation that are dependent in part, on caveolin-1 expression.